2006
DOI: 10.1016/j.jacc.2006.04.091
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Flutter in Infants

Abstract: Infants with AFL usually present within the first 2 days of life. No association was found with structural heart disease. Direct current cardioversion appears to be most effective at establishing sinus rhythm. Chronic AFL has the potential to cause cardiovascular compromise. Atrial flutter in the absence of other arrhythmias has a low risk of recurrence. Once in sinus rhythm, infants with AFL have an excellent prognosis and may not require chronic antiarrhythmic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
3
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 12 publications
0
105
3
10
Order By: Relevance
“…Intrathoracic procedures may add to this risk, with incidental mechanical contact with the neonatal atria triggering an arrhythmia. (Estlin et al, 1998;Gilbert-Barness & Barness 2006;Texter et al, 2006). The increased risk with neonates is not just limited to their small size and relative fragility, however.…”
Section: Atrial Fibrillation In Neonatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrathoracic procedures may add to this risk, with incidental mechanical contact with the neonatal atria triggering an arrhythmia. (Estlin et al, 1998;Gilbert-Barness & Barness 2006;Texter et al, 2006). The increased risk with neonates is not just limited to their small size and relative fragility, however.…”
Section: Atrial Fibrillation In Neonatesmentioning
confidence: 99%
“…It is felt that the immature myocardium, and specifically the atrioventricular node, is also more suited to conduct rapidly, and therefore set the neonate at particularly high risk for rapid ventricular response of any atrial tachyarrythmia, which in turn puts the infant at high risk for a sudden and precipitous drop in cardiac output. If the resultant cardiac output is insufficient for tissue oxygen delivery, the affected infant will then be at significant risk for both developing an irrecoverable rhythm and having end organ damage if the rhythm is not converted in a timely fashion.The largest study of neonates to date identified 50 children over a 25 year period that entered into atrial flutter (seen more often than atrial fibrillation in neonates) with no prior cardiac surgery and only an atrial septal defect found as an associated congenital defect (Texter et al, 2006). There were excellent results with electrical cardioversion (20 of 23, 87%), moderate success with transesophageal pacing (7of 22, 32%), and only 7 of 50 (14%) who required chronic antiarrhythmic therapy.…”
Section: Atrial Fibrillation In Neonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the infants with decreased ventricular function, all recovered normal function after conversion to sinus rhythm. If patients had additional arrhythmia, recurrence of atrial flutter was more likely (Texter et al 2006). Atrial flutter persisting over a long period of time can evolve into atrial fibrillation (Waldo 2004).…”
Section: Management and Prognosismentioning
confidence: 99%
“…Atrial flutter persisting over a long period of time can evolve into atrial fibrillation (Waldo 2004). 5.1.6.5 Clinical presentation: In neonates, 80% are asymptomatic and 20% may present with congestive heart failure (Texter et al 2006). Older patients can experience palpitations, dizziness, chest tightness, chest pain, shortness of breath, and fatigue.…”
Section: Management and Prognosismentioning
confidence: 99%